2014
DOI: 10.1007/s00436-014-3877-x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis sinensis is the most prevalent thick-walled Sarcocystis species in beef on sale for consumers in Germany

Abstract: Bovines are intermediate hosts of Sarcocystis cruzi, Sarcocystis hirsuta, and Sarcocystis hominis, which use canids, felids, or primates as definitive hosts, respectively. Cattle represent also intermediate hosts of Sarcocystis sinensis, but the definitive hosts of this parasite are not yet known. Sarcocystosis in cattle is frequently asymptomatic. The infection is characterized by the presence of thin-walled (S. cruzi) or thick-walled muscle cysts or sarcocysts (S. hominis, S. sinensis, and S. hirsuta). Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 24 publications
4
41
0
1
Order By: Relevance
“…There is a debate whether the Sarcocystis species in cattle and buffaloes are the same species (Jehle et al 2009;Chen et al 2011;Gjerde, 2013;Dubey et al 2014;Moré et al 2014). However, there is general agreement that S. fusiformis of the water buffalo is distinctive and has no morphological equivalent in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…There is a debate whether the Sarcocystis species in cattle and buffaloes are the same species (Jehle et al 2009;Chen et al 2011;Gjerde, 2013;Dubey et al 2014;Moré et al 2014). However, there is general agreement that S. fusiformis of the water buffalo is distinctive and has no morphological equivalent in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…This finding should be considered by the veterinary organization due to the fact that S. cruzi has severe pathogenicity in livestock and can cause severe clinical sign, abortion, and loss of animal products, however, without any pathologic effects on the human population. Controversy, Agholi et al described that S. cruzi was detected in fecal samples of one women immunocompromised patient (HIV positive) using 18S r DNA gene amplifying and phylogenic analysis (24). The S. cruzi has worldwide distribution and is frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…The contradictory results indicated that these serologic techniques cannot be considered as gold standards for the identification of sarcocystosis. A new report suggested a high prevalence of S. hominis in the European beef market (More et al., ). Meat specimens from different supermarkets and butcheries in Germany were evaluated by microscopic and molecular methods including conventional and multiplex real‐time PCR.…”
Section: Helminthsmentioning
confidence: 99%